High Bilateral Amputations and Dismounted Complex Blast Injury (DCBI). (5th September 2018) - Gordon, Wade; Talbot, Max; Fleming, Mark; Shero, John; Potter, Benjamin; Stockinger, Zsolt T
Abstract: High, combat-related bilateral lower extremity amputations rarely occur in isolation. Dismounted complex blast injury is a devastating and life-threatening constellation of multisystem injuries most commonly due to dismounted contact with improvised explosive devices. Rapid damage control resuscitation and surgery are essential to improve patient survival and minimize both early complications and late sequelae. A coordinated team approach is essential to provide simultaneous airway management, volume resuscitation (ideally with whole blood or ratio transfusion), and immediate control of life-threatening hemorrhage. Temporary aortic or iliac vessel clamping during concurrent exploratory or vascular control laparotomy is frequently required. Stabilization of unstable pelvic fractures is then performed, followed by debridement and irrigation of all wounds, which should be left open, and subsequent provisional stabilization of long bone fractures. The goal of the initial surgical resuscitative endeavor is rapid concurrent control of all sources of hemorrhage to avoid the lethal triad of acidosis, hypothermia and coagulopathy. To this end, multiple surgeons or surgical teams should be utilized whenever feasible. Patients then require ongoing resuscitation followed by early and frequent return to the operating suite throughout the evacuation chain. Utilizing this approach, a high survival rate with reasonable functional outcomes is achievable despite the extreme severity of the DCBI pattern.